Spatial distribution patterns of trees in a seasonally dry forest in the Cerros de Amotape National Park, northwestern Peru - Linares-Palomino, Reynaldo (2005)
A study to reveal spatial distribution patterns in four characteristic dry forest tree species was undertaken in six one-hectare plots in the Cerros de Amotape National Park, northwestern Peru. The modified Ripley’s K statistic was used. Eriotheca ruizii (K. Schum.) A. Robyns (Bombacaceae), Bursera graveolens (Kunth) Triana & Planch. (Burseraceae), Caesalpinia glabrata Kunth (Leguminosae) and Cochlospermum vitifolium (Willd.) Spreng. (Cochlospermaceae) present in 11 out of 17 cases, patterns that are not significantly different from a completely random pattern. At the analysed spatial scale, this disagrees with the widely held notion that tropical tree species present clumped patterns. The different factors that may contribute to the observed patterns are discussed.